STUDI KASUS SDN SUNGAI MIAI 4 BANJARMASIN: IMPLEMENTASI MEDIA DIORAMA LETAK WILAYAH DALAM PEMBELAJARAN IPAS - Ferdiyansyah, Aldy; Nafisah, Ainun; Erisa, Nurul; Sari Pera Ayu, Eka; Alviannor, Muhammad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the limited use of concrete and interactive learning media in IPAS (Natural and Social Sciences) instruction, which has led to low student understanding of the concept of administrative region levels in grade 3. Therefore, this study aims to examine the implementation of concrete media in the form of a territorial diorama at SDN Sungai Miai 4 Banjarmasin. The research uses a qualitative descriptive approach with a case study method. Data were collected through observation, interviews, and documentation. The findings show that the diorama media effectively enhances student engagement and comprehension by providing a concrete and contextual visualization of regional structures from the neighborhood (RT) level up to the provincial level . Students became more enthusiastic, actively engaged in discussions, and were able to explain the concepts more accurately. Challenges identified include space limitations and the maintenance of physical media. Nonetheless, the diorama proved to be an effective solution for meaningful IPAS learning, especially for lower-grade students who require concrete approaches suited to their cognitive development stage